The Perception of Islamic Youth to The Phenomenon of Hubbu Ilahi - Muhammad Roy Asrori; Zakiyatul Fitriyah; Ahmad Faikul Anam; Ahmad Nashih Anis Zubaidy; Zubaidah Zubaidah (International Journal of Islamic Khazanah, 2021)
Youth life is closely related to spiritual activity. The phenomenon that is still encountered is Hubbu Ilahi, or the love attitude of Allah SWT. This phenomenon is presumed that adolescents only state and do not know the consequences of their attitudes. So, this study aims to determine the perceptions of today's adolescents on the phenomenon of Hubbu Ilahi. This research is descriptive qualitative research with a survey research method. This study used a purposive random sampling technique to 39 adolescents. Data collection used a questionnaire with the google form platform. Then, the data were analyzed using: data presentation, data reduction, and concluding. The results showed that adolescent respondents stated the consistency of love of the Quran, love of Rasulullah (SAW), love of the Prophet's Sunnah, and love of the Akhirat life. However, the busyness of the world blocks the proven proof of love. The analysis concluded that only 7.7% of adolescents fit Hubbu Ilahi's criteria.